Effect of bulky side groups on photophysical properties and electroluminescent performance of oligo(styryl)benzenes. (May 2023) - de Lera-Garrido, Fernando; Domínguez, Rocío; Fernández-Liencres, M. Paz; Martín, Cristina; Tolosa, Juan; García-Frutos, Eva M.; Perles, Josefina; Hofkens, Johan; García-Martínez, Joaquín C.; Garzón-Ruiz, Andrés; Navarro, Amparo
Abstract: The rational design of electroluminescent compounds has been recognized as a promising strategy to maximize the efficiency of electronic devices. In this work, we analyze the impact of the substitution of n -alkyl and n -alkoxy side chains by bulkier side groups ( tert -butyl and tert -butoxy) on the photophysics of the two model fluorophores 1, 3, 5-tris(styryl)benzene and 1, 2, 4, 5-tetra(styryl)benzene. We found that the bulky side groups have a significant contribution to the vibrational normal modes associated with the non-radiative deactivation. The aggregation-induced enhanced emission phenomenon observed in some cases was attributed to the blocking of the trans→cis photoisomerization and the restriction of intramolecular vibrations. In the solid state, the bulky side groups have demonstrated to play a determining role in the supramolecular structure and photophysical properties, particularly in the case of the tetra(styryl)benzenes. In light-emitting devices, we found that the incorporation of the bulky side groups in oligo(styryl)benzenes could reduce the electromer formation and improve the device performance. The tetra(styryl)benzenes, and particularly the tert -butyl derivative, showed better device performance, with lower turn-on voltage, higher current density and electroluminescent intensity. Graphical abstract: Image 1